The Effects of Intellectual Capital on Performance in Australian Small and Medium Enterprises (SMEs) - Khan, Y.; Terziovski, Mile (ANZAM, 2014)
There are limited studies in the literature that investigate the relationship between intellectual capitaland SME Performance, and test the mediating effects of organizational innovation. This studyexamined 2,154 SMEs of various industries from 2009-2011 by using Business Longitudinal Database (BLD) from the Australian Bureau of Statistics (ABS).Our research findings show that human, structural, and relational capital has a positive and significant effect on SME performance when mediated by organizational innovation. The implication of our findings is that managers should simultaneously develop their human capital through training, improve their networking andcollaboration, and increase their investment in information technology in order to improve SMEperformance through innovation.